Assessing soil biological properties of natural and planted forests in the Malaysian tropical lowland dipterocarp forest - Karam Singh, Daljit Singh; Abdu, Arifin; Othman, Radziah; Jusop, Shamsuddin; Abdul Hamid, Hazandy; Nik Ab. Majid, Nik Muhamad; Panicker, Mohanaselvi; Abd. Halim, Nor Halizah (Science Publications, 2011)
Problem statement: A study was conducted to evaluate and compare the soil biological properties of a natural forest and an 18-year-old stand of Shorea leprosula in Chikus Forest Reserve, Perak, Malaysia. Approach: Soils were sampled at depths of 0-15 cm (topsoil) and 15-30 cm (subsoil) in six subplots (20×20 m) of natural forest (C1) and of a planted S. leprosula (C2) plot. Fresh composite soil samples were kept in UV-sterilized polyethylene bags prior to analysis in the laboratory. The microbial population count was determined using a spread-plate count technique. The microbial enzymatic activity was elucidated using a Fluorescein Diacetate (FDA) hydrolysis assay; microbial biomass was extracted using a rapid chloroform fumigation extraction method. The Microbial Biomass C (MBC) was determined by wet dichromate oxidation; Kjeldahl digestion and a distillation method were used for evaluation of Microbial Biomass N (MBN). Results: Results indicate that only the microbial biomass N and the population count in the soil at the 0-15 cm depth were found to be higher in C1 compared to C2. The higher microbial population count in the soil at the 0-15 cm depth of C1 compared to C2 was enhanced by the large amount of organic matter that serves as a suitable medium for soil microbial growth. The higher MBN in the C1 soil was also influenced by the high content of organic material available that encourages activities of decomposing bacteria to take place. Similarities in the soil biological properties of the plots with regard to enzymatic activity and microbial biomass Care believed to be influenced by the same topographic gradient. The higher MBC/MBN ratios found in soils of C2 compared to C1 were due to the low availability of N compared to C, might result from N utilization by soil microbes for organic material decomposition. Conclusion: There are similarities in microbial enzymatic activity and biomass C, but not in microbial population counts and biomass N, between a natural forest and an 18-year-old stand of S. leprosula in Chikus Forest Reserve, Perak, Malaysia.